STE(AI)ming across disciplines and into the future: Generative artificial intelligence for ethics, access, and interdisciplinary skills development in classrooms and communities - Caines, Rebecca (American Journal of STEM Education, 2026)
This paper shares the results of a research creation study, examining GenAI use in interdisciplinary STEM/STEAM classrooms. It outlines curricular examples developed for a university education setting and discusses the potential for the use of GenAI tools in wider, community-engaged research. The author argues that careful implementation of these tools can help teachers and learners to engage with questions of ethics in technology contexts and offer new forms of access to technical and creative training in cross-disciplinary learning environments. The paper proposes that informed and careful use of GenAI tools can contribute to helping grow “improvisatory” STEAM skillsets for both teachers and students including self-directed learning, collaboration, responsibility, curiosity, and play.